Remote sensing for three-dimensional modelling of hydromorphology - Flener, Claude (fi=Turun yliopisto|en=University of Turku|, 2015)
Successful management of rivers requires an understanding of the fluvial processes that govern them. This, in turn cannot be achieved without a means of quantifying their geomorphology and hydrology and the spatio-temporal interactions between them, that is, their hydromorphology. For a long time, it has been laborious and time-consuming to measure river topography, especially in the submerged part of the channel. The measurement of the flow field has been challenging as well, and hence, such measurements have long been sparse in natural environments. Technological advancements in the field of remote sensing in the recent years have opened up new possibilities for capturing synoptic information on river environments. This thesis presents new developments in fluvial remote sensing of both topography and water flow. A set of close-range remote sensing methods is employed to eventually construct a high-resolution unified empirical hydromorphological model, that is, river channel and floodplain topography and three-dimensional areal flow field. Empirical as well as hydraulic theory-based optical remote sensing methods are tested and evaluated using normal colour aerial photographs and sonar calibration and reference measurements on a rocky-bed sub-Arctic river. The empirical optical bathymetry model is developed further by the introduction of a deep-water radiance parameter estimation algorithm that extends the field of application of the model to shallow streams. The effect of this parameter on the model is also assessed in a study of a sandy-bed sub-Arctic river using close-range high-resolution aerial photography, presenting one of the first examples of fluvial bathymetry modelling from unmanned aerial vehicles (UAV). Further close-range remote sensing methods are added to complete the topography integrating the river bed with the floodplain to create a seamless high-resolution topography. Boat- cart- and backpack-based mobile laser scanning (MLS) are used to measure the topography of the dry part of the channel at a high resolution and accuracy. Multitemporal MLS is evaluated along with UAV-based photogrammetry against terrestrial laser scanning reference data and merged with UAV-based bathymetry to create a two-year series of seamless digital terrain models. These allow the evaluation of the methodology for conducting high-resolution change analysis of the entire channel. The remote sensing based model of hydromorphology is completed by a new methodology for mapping the flow field in 3D. An acoustic Doppler current profiler (ADCP) is deployed on a remote-controlled boat with a survey-grade global navigation satellite system (GNSS) receiver, allowing the positioning of the areally sampled 3D flow vectors in 3D space as a point cloud and its interpolation into a 3D matrix allows a quantitative volumetric flow analysis. Multitemporal areal 3D flow field data show the evolution of the flow field during a snow-melt flood event. The combination of the underwater and dry topography with the flow field yields a compete model of river hydromorphology at the reach scale.

Jokien onnistunut hallinta edellyttää virtavesien prosessien ymmärtämistä. Tämä ei ole mahdollista ilman jokien geomorfologian ja hydrologian kvantifiointia sekä niiden spatiotemporaalisten suhteiden tutkimista, eli jokien hydromorfologiaa. Joen topografian mittaaminen, varsinkin uoman vedenalaisen osalle on pitkään ollut työlästä ja aikaa vievää. Virtauskentän kattava mittaaminen on myös ollut haastavaa, sillä seurauksella, että niitä on tehty harvakseltaan luonnollisessa ympäristössä. Viimeaikainen teknologinen kehitys kaukokartoituksessa on mahdollistanut synoptisen tiedon mittaamisen jokiympäristöissä. Tässä väitöstutkimuksessa on kehitetty virtavesien kaukokartoitusta sekä jokien topografian että virtausmittauksen alalla. Useita eri lähikaukokartoitusmenetelmiä yhdistämällä on tehty korkean resoluution yhtenäinen empiirinen malli joen hydromorfologiasta, eli joen uoman ja tulvatasangon topografiasta ja kolmiulotteisesta virtaamakentästä. Empiriaan ja hydrauliseen teoriaan perustuvat optisen kaukokartoituksen menetelmiä testattiin ja arvioitiin käyttämällä normaaliväri-ilmakuvia, kaikuluotain kalibrointia ja referenssimittauksia kivipohjaisessa subarktisessa joessa. Empiiristä optista syvyysmallia kehitettiin edelleen lisäämällä syvän veden säteilyparametrin arviointialgoritmi, joka mahdollisti mallin käytön myös matalavetisissä jokiuomissa. Parametrin vaikutus malliin arvioitiin korkean resoluution matalailmakuvista hiekkapohjaisessa subarktisessa joessa yhdessä ensimmäisistä syvyysmalleista, joka on tehty käyttäen kauko-ohjattua minihelikopteria (eng.UAV, Unmanned Aerial Vehicle). Lähietäisyyden kaukokartoitusmenetelmiä käytettiin edelleen topografisen mallin täydentämiseen, integroimalla joen uoma ja tulvatasanko yhtenäiseksi korkean resoluution topografiaksi. Mobiilia laserkeilausta käytettiin vedenpinnan yläpuolisen osan topografian mittaamiseen korkealla resoluutiolla vene- kärry- ja reppupohjaisten kartoitusalustojen avulla. Monen ajankohdan mobiilin laserkeilauksen ja UAVfotogrammetrian tarkkuutta arvioitiin maalaserikeilausaineiston avulla. Laserkeilattu ja fotogrammetrinen aineisto yhdistettiin, jolloin saatiin kahden vuoden ajalta saumaton digitaalinen maastomalli. Mallin avulla oli mahdollista arvioida koko joen uoman korkean resoluution muutosanalyysin metodologiaa. Kaukokartoitukseen perustuvaa hydromorfologista mallia täydennettiin uniikilla virtauskentän kolmiulotteisella kartoitusaineistolla. Kauko-ohjattavaan veneeseen asennettu akustinen virtausmittauslaite yhdessä tarkan satelliittipaikannusjärjestelmän kanssa mahdollistivat alueellisesti valikoitujen kolmiulotteisten virtausvektoreiden sijainnin määrittämisen kolmiulotteisessa avaruudessa pistepilvenä. Tämän aineiston kolmiulotteinen interpolaatio matriisiksi mahdollisti edelleen volymetrisen virtausanalyysin. Monen ajankohdan alueellinen kolmiulotteinen virtauskenttä osoitti virtausolosuhteiden evoluution kevättulvassa. Vedenalaisen ja kuivan maan topografia yhdessä jokiuoman virtauskenttien kanssa muodosti kattavan mallin joen hydromorfologiasta.